2018
DOI: 10.1177/1078155218811505
|View full text |Cite
|
Sign up to set email alerts
|

Cetirizine versus diphenhydramine in the prevention of chemotherapy-related hypersensitivity reactions

Abstract: Objective This study evaluated the role of cetirizine compared to diphenhydramine as premedications for patients receiving paclitaxel, cetuximab, and rituximab infusions. Historically, diphenhydramine has been linked with more sedation in comparison to cetirizine; however, it is unknown if cetirizine can replace diphenhydramine in the prevention of hypersensitivity reactions in patients receiving chemotherapy. Methods This is a retrospective study designed to assess infusion reactions occurring in patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…There are strengths and limitations to our design. Though oncology clinics may have already adopted different strategies to decrease side-effects from diphenhydramine based on experience or changes in practice, this prospective randomized trial design offers stronger internal validity compared with retrospective or observational designs [ 12 , 13 ]. The performance of recruitment for eligible patients was higher than previously reported (73 vs 60%, respectively) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are strengths and limitations to our design. Though oncology clinics may have already adopted different strategies to decrease side-effects from diphenhydramine based on experience or changes in practice, this prospective randomized trial design offers stronger internal validity compared with retrospective or observational designs [ 12 , 13 ]. The performance of recruitment for eligible patients was higher than previously reported (73 vs 60%, respectively) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also the dosage that is recommended in the monograph [ 4 ]. Oral cetirizine 10 mg was selected as a comparator namely for the advantageous pharmacokinetics and pharmacodynamics properties found at this dose and the real-life experience described by Durham et al in more than 35 paclitaxel-naïve patients [ 13 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived quicker onset of action of older AHs is often cited as a reason why patients and practitioners choose first-generation medications, however this perception has been proven inaccurate in clinical studies [33, 41]. Indeed, in a double-blind placebo controlled trial, both cetirizine and loratadine were found to have significantly faster onset of action, potency, and duration of action when compared to chlorpheniramine [42].…”
Section: Newer Generation H1-antihistaminesmentioning
confidence: 99%